PELAKSANAAN PENDIDIKAN KEPADA ANAK PENYANDANG KANKER DI YAYASAN KASIH ANAK KANKER RIAU PEKANBARU - Saputra, Andi; Ayub, Daeng (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study in the background “sekolah-ku” program in by Foundation Of The Cancer Riau Pekanbaru affiliation of Foundation Of The Cancer Indonesia. Education given free for children cancer patients who are in the hospital. Problem this research is how the implementation of eduction to children with cancer in Foundation Of The Cancer Riau Pekanbaru?. The purpose of the research to determine the implementation of education to the cancer. The kind of this research is fenomenologi wuth the approach kualitatif. Informants this study of 3 people, 1 informant core, 1 informant control, and 1 informant observers. Data collection instruments consisted of the researchers them selves and interview guide consisted of 30 questions. The implementation of education namely teachers, students, the mean and infrastructure, the activities of learning teaching, and the cost of. If one componenn is not fulfilled then education can not in carried out.Key Words: Implementation of Education, Children with Cancer